The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1180/claymin.2014.049.3.04
|View full text |Cite
|
Sign up to set email alerts
|

The Fe-Mg-saponite solid solution series – a hydrothermal synthesis study

Abstract: The boundary conditions of saponite formation are generally considered to be well known, but significant gaps in our knowledge persist in respect to the influence of solution chemistry, temperature, and reaction time on the mineralogy, structure, stability, and chemical composition of laboratory-grown ferrous saponite. In the present study, ferrous saponite and Mgsaponite were synthesized in Teflon-lined, stainless steel autoclaves at 60, 120 and 180°C, alkaline pH, reducing conditions, and initial solutions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 52 publications
1
68
1
5
Order By: Relevance
“…The TEM-EDX spectra were acquired using a counting time of 30 s to reduce element migration and element loss. The accuracy of the EDX results was verified by replicate measurements performed on a suite of phyllosilicate standards [26][27][28]. The analytical error was determined to be ± 2 at.% for Si and Al analyses.…”
Section: Solid-phase Characterizationmentioning
confidence: 85%
“…The TEM-EDX spectra were acquired using a counting time of 30 s to reduce element migration and element loss. The accuracy of the EDX results was verified by replicate measurements performed on a suite of phyllosilicate standards [26][27][28]. The analytical error was determined to be ± 2 at.% for Si and Al analyses.…”
Section: Solid-phase Characterizationmentioning
confidence: 85%
“…Each of the smectites with high octahedral Al (E and F) has low octahedral site occupancies (2.57 and 2.53, respectively). Calculated octahedral site occupancies below three are common in synthetic trioctahedral smectites [ Baldermann et al ., ; Grauby et al ., ]. These low occupancies indicate a ditrioctahedral structure characterized by vacancy defects associated with trivalent Al 3+ cations in the octahedral sheet.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work related to Fe-rich ferrous smectites includes both synthetic and natural samples, with characterization largely confined to major element and X-ray diffraction (XRD) analyses with limited Mössbauer and spectral reflectance analyses [Badaut et al, 1985;Baldermann et al, 2014;Chukanov et al, 2003;Harder, 1978;Lajarige et al, 1998;Parthasarathy et al, 2003]. There are Mars-relevant gaps in chemistry (particularly high-MgO and low-Al 2 O 3 ferrous smectite), and, for spectral reflectance studies, the reported wavelength ranges do not overlap those covered by the hyperspectral imaging instruments in Martian orbit (effectively~0.40 μm to 2.6 μm [e.g., Murchie et al, 2007]).…”
Section: Introductionmentioning
confidence: 99%
“…About 50 mg of the sample was mixed with 5 mL of deionised water, following dispersion for 10 min in an ultrasonic bath. The clay-in-suspension was then sucked through a ceramic tile of about 4 cm 2 in order to produce oriented specimens (Baldermann et al 2014). These clay films were X-rayed from 3 to 30° 2θ with a step size of 0.02° 2θ and a count time of 2 s per step, each at air-dried states and after the solvation of the clay matter with ethylene glycol (EG) and heating of the preparations to 550 °C for 1 h. The percentage of illite layers (%I) in illite–smectite (I-S) mixed layered clay minerals was determined based on EG-solvated patterns with an analytical precision of ±5% (Baldermann et al 2013).…”
Section: Methodsmentioning
confidence: 99%